2019
DOI: 10.1093/oso/9780198833079.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Internet Governance

Abstract: What is at stake for how the Internet continues to evolve is the preservation of its integrity as a single network. In practice, its governance is neither centralized nor unitary; it is piecemeal and fragmented, with authoritative decision-making coming from different sources simultaneously: governments, businesses, international organizations, technical and academic experts, and civil society. Historically, the conditions for their interaction were rarely defined beyond basic technical coordination, due at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…The growing boundary permeability noted by hybrid governance scholars concerns not only sectors, but also practices and, crucially, knowledge. The enduring concentration of emerging technology expertise in private hands (Radu, 2019;Radu et al, 2014) is further accentuated. This complements more advanced commercial strategies of companies driving AI innovation, generally consolidating their position around two poles of (digital) power.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing boundary permeability noted by hybrid governance scholars concerns not only sectors, but also practices and, crucially, knowledge. The enduring concentration of emerging technology expertise in private hands (Radu, 2019;Radu et al, 2014) is further accentuated. This complements more advanced commercial strategies of companies driving AI innovation, generally consolidating their position around two poles of (digital) power.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the rules and ethics directions are not contradictory and could potentially coexist, they represent regulatory regimes built on different values and trust systems. The general reluctance to regulate AI at an early stage is reminiscent of the approach chosen for regulating the Internet only when security and legal problems became widespread (Radu, 2019). It is also tightly linked to the fear of stifling innovation and the complex management of uncertainties inherent to new technologies, explicitly mentioned in some of the strategies.…”
Section: Variation In the National Ai Approaches: New Roles And Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud services and content delivery networks all rely on the DNS, making the web experience as we know it today highly dependent on a technical functionality that has remained hidden in the technical layer and relatively abstruse in public discussion. With the exception of the political negotiations around the domain name registration system in particular the creation and subsequent reform of the Internet Corporation for Assigned Names and Numbers (ICANN), the non-profit private American corporation that oversees the management of the DNS (Mueller 2004;Radu 2019)the dynamics in the domain name market and its recent concentration trends have not received enough scholarly attention. Significant exceptions include recent studies by Borgolte et al (2019) and Huston (2019), who started to shed light on effects that go beyond the technical aspects, assessing legal, economic and political consequences.…”
Section: The Dns Market Over Timementioning
confidence: 99%
“…At the same time, intermediaries enforcing their own policies around health disinformation may pay little attention to protecting media freedom and pluralism. My previous research showed that reigning in disinformation on social platforms is part and parcel of broader internet governance transformations which started in 2016 ( Radu, 2019 ). During the COVID-19 crisis, stronger national approaches emerged and technology corporations acquired increased power as intermediaries that screen and take down content, in many cases in automated ways.…”
mentioning
confidence: 99%